Radio frequency interference: The study of rain effect on radio signal attenuation = [Interferens frekuensi radio: Kajian kesan hujan pada pengecilan isyarat radio] - Umar, R.; Sulan, S.S.; Azlan, A.W.; Ibrahim, Z.A.; Wan Mokhtar, W.Z.A.; Sabri, N.H. (Malaysian Society of Analytical Sciences, 2015)
The intensity of radio waves received by radio telescopes is always not subject to human control. In the millimetre band, the propagation of the electromagnetic waves is severely affected by rain rate, dust particle size and drop size in the terms of attenuation, noise and depolarization. At the frequency above 10 GHz, the absorption and scattering by rain cause a reduction in the transmitted signal amplitude which will lead to the reducing of the availability, reliability and performance on the communications link. In this study, the rain effect on radio signal has been investigated. Spectrum analyzer and weather stations were used to obtain the RFI level and rain rate data respectively. The radio frequency interference (RFI) pattern due to rain factor was determined. This will benefit radio astronomer in managing sites for radio observation for radio astronomy purposes.